Electronic alerts for acute kidney injury across primary and secondary care. Issue 2 (10th May 2021) - Barker, Joseph; Smith-Byrne, Karl; Sayers, Oliver; Joseph, Krishan; Sleeman, Mark; Lasserson, Daniel; Vaux, Emma
Abstract : Problem: In 2009 the National Confidential Enquiry into Patient Outcome and Death suggested only 50% of patients with acute kidney injury (AKI) receive good standards of care. In response National Health Service (NHS) England mandated the use of electronic AKI alerts within secondary care. However, we recognised AKI is not just a secondary care problem, where primary care has a crucial role to play in prevention, early detection and management as well as post-AKI care. Methods: AKI alerts were implemented in primary and secondary care services for a population of 480 000. Comparisons were made in AKI incidence, peak creatinine following AKI and renal recovery in the years before and after using Byar's approximation (95% CI). Intervention: A complex quality improvement initiative was implemented based on the design and integration of an AKI alerting system within laboratory information management systems for primary and secondary care, with an affixed URL for clinicians to access a care bundle of AKI guidelines on safe prescribing, patient advice and early contact with nephrology. Results: The intervention was associated with an 8% increase in creatinine testing (n=32 563). Hospital acquired AKI detection increased by 6%, while community acquired AKI detection increased by 3% and AKI stage 3 detected in primary care fell by 14%. The intervention overall had no effect on AKI severity but did improve follow-up testing and renal recovery. Importantly hospital AKI 3 recoveries improved by 22%. In a small number of AKI cases, the algorithm did not produce an alert resulting in a reduction in follow-up testing compared with preintervention levels. Conclusion: The introduction of AKI alerts in primary and secondary care, in conjunction with access to an AKI care bundle, was associated with higher rates of repeat blood sampling, AKI detection and renal recovery. Validating accuracy of alerts is required to avoid patient harm.